Performance Evaluation of a Two Hole and Five Hole Flow Analyzer for Subsonic Flow - Akhila Rupesh, Dr. J V MurugaLal Jeyan (International Journal of Advanced Science and Technology, 2020)
Flow analysis over a desired object is considered as to be a great significance because, the aerodynamic nature of an object to be experimented depends on the flow analysis over that object. Here in the area of Aerodynamics, wind tunnel is used as an instrument to test the flow analysis over the object that we desire. Hence, calibration process of the wind tunnel has to be conducted with more care. The test section of the wind tunnel where the models to be tested are kept should always provide uniform and as well as laminar flow during the flow parameter ascertainment for furnishing exact results. But generating a perfect laminar flow throughout the test facility of the wind tunnel is nearly not possible. Hence, before going ahead with the experiment, an immense focus should be provided on the wind tunnel calibration part. In general, a pitot static tube is used in the subsonic wind tunnel for the calibration. But because of poor accuracy and low sensitivity of the pitot static tube, Invention of new instruments for the calibration is being made. Hence, in this paper, we are going to discuss such instrument’s design and analysis used for wind tunnel calibrations i.e., two hole and five hole flow analyzer.